2007
DOI: 10.1016/j.neuropsychologia.2006.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of form-from-motion perception in human extrastriate cortex

Abstract: The exquisite sensitivity of the human visual system to form-from-motion (FfM) cues is well documented. However, identifying the neural correlates of this sensitivity has proven difficult, particularly determining the respective contributions of different motion areas in extrastriate visual cortex. Here we measured visual FfM perception and more elementary visual motion (VM) perception in a group of 32 patients suffering from acute posterior brain damage, and performed MRI-based lesion analysis. Our results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…is a 47-year-old, right-handed man suffering from dementia affecting primarily visuospatial functions as revealed by extensive neuropsychological testing. He exhibited a severe impairment for direction discrimination from coherent motion and orientation discrimination of twodimensional forms-from-motion (Blanke et al 2007). However, neuropsychological testing did not reveal any object recognition deficits, and so we were interested to know whether he could use three-dimensional SFM cues by a system other than his impaired dorsal stream.…”
Section: Akinetopsic Patientmentioning
confidence: 99%
“…is a 47-year-old, right-handed man suffering from dementia affecting primarily visuospatial functions as revealed by extensive neuropsychological testing. He exhibited a severe impairment for direction discrimination from coherent motion and orientation discrimination of twodimensional forms-from-motion (Blanke et al 2007). However, neuropsychological testing did not reveal any object recognition deficits, and so we were interested to know whether he could use three-dimensional SFM cues by a system other than his impaired dorsal stream.…”
Section: Akinetopsic Patientmentioning
confidence: 99%
“…Despite the evidences confirming their segregation, recent findings [8,9,10] attest the relevance of the interaction between the dorsal and the ventral stream using stimuli which enhance both M-and P-pathways, such as form-frommotion and biological motion stimuli. These stimuli require the integration of the motion perception to detect the form of an object.…”
Section: Introductionmentioning
confidence: 90%
“…These stimuli require the integration of the motion perception to detect the form of an object. Several neuropsychological studies have shown that the perception of form created from moving stimuli (form-from-motion) is mediated by specific neural pathways [8,9,10], involving the connections between the M-and Psystems. It is indeed likely that form-from-motion perception can persist despite impaired perception of static form or motion [for a review see ref .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations